Narrative Substrata in an Albanian Poem: A Cross-Cultural Perspective on Shared Motifs - Alija, Ermira; Hysaj, Denisa (Technium Social Sciences Journal, 2025)
This article examines the narrative core of the Albanian literary work Erveheja by Muhamet Kuçuku, written around 1820, which, according to the author himself, was influenced by an earlier Turkish source. The aim of the study is to trace the intertextual origins of this subject and to provide a comparative analysis focused on the narrative motifs of the shared subject, taking into account the Tuti-nama (12th century) and a Kazakh folktale (15th century). The methodology combines hermeneutic and structuralist analysis, with an emphasis on the meaning, function, and transmission of motifs, as well as their connection to the folkloric and cultural dimension. The analysis of motifs and their comparison highlight early narrative structures that have remained unchanged, as well as elements that have been transformed and acquired didactic-religious connotations. The findings suggest that the subject of Erveheja embodies elements of an intercultural narrative archetype. Furthermore, its mystical-religious approach, in which the extraordinary and miraculous are attributed to God and the heroine’s morality is identified with Divine morality, has contributed to shaping Erveheja as a cultural model and may have played a decisive role in preserving its subject intact over time.